Langue sacrée, langue parlée - Aviv, Nurith; Marom, Itai (Nurith Aviv, 2011)
Talking Hebrew in the street, writing fiction and poetry in Hebrew, even gossiping in Hebrew were all unimaginable before the grand project of Zionism set out to revive the sacred language and turn it into Israel’s everyday language. What has happened to Hebrew in the process and what happens to the people for whom it became a mother tongue? What traces has the language of the sacred text left and how do they resonate in everyday life? In Nurit Aviv’s poetic documentary, Israeli writers and artists attempt to describe their relationship to the religious dimension of the Hebrew language. Poetry, politics, religion and secular life are all explored in the most intriguing way through well-crafted interviews that narrate one of Israel’s most fascinating and least explored undercurrents. [ukjewishfilm.org]